Enhanced Carbapenem Resistance through Multimerization of Plasmids Carrying Carbapenemase Genes - Ryuichiro Abe; Yukihiro Akeda; Yo Sugawara; Yuki Matsumoto; Daisuke Motooka; Ryuji Kawahara; Norihisa Yamamoto; Kazunori Tomono; Tetsuya Iida; Shigeyuki Hamada (mBio, 2021)
We demonstrated the multimerization of plasmids harboring carbapenemase genes, and multimeric plasmids of various discrete sizes existed in a host bacterial cell of Escherichia coli